2021
DOI: 10.1038/s41467-021-23782-w
|View full text |Cite
|
Sign up to set email alerts
|

Feeding diversified protein sources exacerbates hepatic insulin resistance via increased gut microbial branched-chain fatty acids and mTORC1 signaling in obese mice

Abstract: Animal models of human diseases are classically fed purified diets that contain casein as the unique protein source. We show that provision of a mixed protein source mirroring that found in the western diet exacerbates diet-induced obesity and insulin resistance by potentiating hepatic mTORC1/S6K1 signaling as compared to casein alone. These effects involve alterations in gut microbiota as shown by fecal microbiota transplantation studies. The detrimental impact of the mixed protein source is also linked with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 57 publications
(69 reference statements)
3
53
0
Order By: Relevance
“…Yogurt consumption preserves glucose homeostasis and insulin sensitivity. Three individual studies were performed to explore the effect of a lyophilized yogurt product (Y) on diet-induced obesity and associated metabolic impairments using a high-fat high-sucrose (H) diet whose protein source was not limited to casein but was a mixed source of protein to be more representative of those consumed by humans 22 (Table 1). The yogurt was administered in the lyophilized form to reach the equivalent of two servings per day, hence replacing 7.6% of the daily energy intake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yogurt consumption preserves glucose homeostasis and insulin sensitivity. Three individual studies were performed to explore the effect of a lyophilized yogurt product (Y) on diet-induced obesity and associated metabolic impairments using a high-fat high-sucrose (H) diet whose protein source was not limited to casein but was a mixed source of protein to be more representative of those consumed by humans 22 (Table 1). The yogurt was administered in the lyophilized form to reach the equivalent of two servings per day, hence replacing 7.6% of the daily energy intake.…”
Section: Resultsmentioning
confidence: 99%
“…Diets were then matched for protein, fat, carbohydrate, and saturated: polyunsaturated fatty acid ratio (SAT: PUFA). For more information, see Choi et al 22 .…”
Section: Methodsmentioning
confidence: 99%
“…BCFA production is protein-specific. Accordingly, changing the protein source from casein to a protein mix resembling a typical WD for human consumption altered the murine gut microbiota to enhance the generation of BCFAs exacerbating diet-induced obesity and hepatic insulin resistance through the mTORC1/S6K1 signaling pathway [ 95 ]. Conversely, substituting the protein source in WDs from casein to whole-cell lysates of the methanotrophic soil bacterium, McB, reversed WD-induced pathogenic traits in mice [ 69 ].…”
Section: Shaping the Gut Microbiotamentioning
confidence: 99%
“…Interestingly, whey protein has also been suggested to modify the microbiota, although not necessarily with beneficial effects [ 247 ]. Indeed, the type of source of proteins and amino acids may also be crucial because two recent studies in obese mice have shown that: i) dietary essential amino acids affect gut microbiota composition and NAA levels in the adipose tissue and plasma of obese mice, thereby enhancing energy expenditure [ 248 ]; and ii) casein proteins instead exacerbate hepatic insulin resistance due to the increased gut microbial branched-chain fatty acids [ 249 ]. Interestingly, both these effects were suggested to be mediated by the activation of mammalian Target Of Rapamycin Complex 1/S6 Kinase 1 (mTORC1/S6K1) signalling in different organs (brown adipose tissue and liver, respectively).…”
Section: Future Directionsmentioning
confidence: 99%